2009
DOI: 10.1177/1352458509102617
|View full text |Cite
|
Sign up to set email alerts
|

Association between MRI parameters and the MS severity scale: a 12 year follow-up study

Abstract: MRI measures of axonal loss are associated with higher overall disease severity in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 36 publications
7
40
3
Order By: Relevance
“…Over time, T2 decreases to that of chronic lesions (84,139,170), similar to the behaviour of T1. One study detected monoexponential relaxation in acute WM lesions, which became bi-exponential during remission, and finally returned to mono-exponential as the lesion turned into a chronic lesion (168).…”
Section: Qmri In Mssupporting
confidence: 61%
See 1 more Smart Citation
“…Over time, T2 decreases to that of chronic lesions (84,139,170), similar to the behaviour of T1. One study detected monoexponential relaxation in acute WM lesions, which became bi-exponential during remission, and finally returned to mono-exponential as the lesion turned into a chronic lesion (168).…”
Section: Qmri In Mssupporting
confidence: 61%
“…Some lesions, when viewed on T1-weighted images, appear hypo-intense compared to surrounding WM ,and the inclusion of T1-weighted imaging may increase the correlation with clinical disability, but only to a limited degree (138,139). Factors believed to explain this discrepancy include cortical reorganisation (140), where other parts of the brain may compensate for focal injury; brain plasticity (141,142), where signal transmissions may use alternative pathways; and the consideration of strategic lesion location (143,144).…”
Section: Mri In Msmentioning
confidence: 99%
“…[11][12][13] In an analysis of multiple studies in MS, a cross-sectional correlation was reported between MRI T 2 parameters and EDSS scores in MS patients at different disease stages (correlation coefficients were 0.15 for secondary progressive MS (SPMS), 0.55 for CIS and 0.60 for relapsing-remitting…”
Section: Methods For General Assessment Of Activities and Social Partmentioning
confidence: 99%
“…12 Another study in The Netherlands showed that during 12 years of follow-up of 46 patients with confirmed MS, increasing lesion loads, atrophy and axonal loss were associated with disease severity as determined by the MS Severity Score (MSSS). 13 The MSSS method is based on the EDSS, but uses an algorithm that incorporates the distribution of disability in patients with similar disease durations.…”
Section: Ms [Rrms]mentioning
confidence: 99%
“…[1][2][3] Instead, brain-tissue loss shows a stronger correlation with disease progression, especially in a later stage of the disease. [3][4][5][6][7][8][9] The key for the practical, clinical application of brain-tissue volume measurements is an automated, fast method that can be integrated into the clinical workflow. Numerous automated methods exist for this purpose, generally based on conventional T1-weighted, T2-weighted, and FLAIR images or a combination thereof.…”
mentioning
confidence: 99%